The ınvestıgatıon of attıtudes to cope wıth stress in terms of dıfferent varıables of physıcal educatıon and sports students - Çetinkaya, Turan; Kırtepe, Abdurrahman (My University, 2018)
The purpose of this study was to examine determination of attitudes to cope with stress of the students in physical education and sports departments. 305 students from, Ahi Evran University, department of pyhsical education and sports teacher, sports management and coaching education department, was participated in this study..In tghe study 43-item attitude of coping with stress inventory and personal information form was used as a data collection tool. For comparison of the obtained data, distribution, frequency, t test and ANOVA analyses were used. The specific structure of the sport field and the positive mental factors that are brought with it stand as important tools for effective stress fighting. The specific structure of the sport field and the positive mental factors that are brought with it stand as important tools for effective stress fighting.As a result of the statistical analyses attitudes to cope with stress did not Show a statistical difference according to all subscales and in terms of gender, department and of sports type variables.
Keywords: Eğitim; Eğitim Araştırmaları; Spor Bilimleri